2019
DOI: 10.1038/s41598-019-39323-x
|View full text |Cite
|
Sign up to set email alerts
|

16S rRNA amplicon sequencing characterization of caecal microbiome composition of broilers and free-range slow-growing chickens throughout their productive lifespan

Abstract: Gut microbiota affects health, metabolism and immunity of the host, and in the case of livestock, also food-safety. Here, 16S rRNA gene high-throughput Illumina sequencing was used to describe the microbiome of chicken caeca in two different breeds and management systems throughout their whole productive lifespan. Broilers (Ross-308), as a fast-growing breed reared in an intensive system for 42-days, and a slow-growing breed of chicken (Sasso-T451A) reared in an extensive farming system with outdoor access for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

34
113
8
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(161 citation statements)
references
References 63 publications
(104 reference statements)
34
113
8
6
Order By: Relevance
“…When analysing the abundance of MAGs between birds from different lines, consuming either a vegetable diet or a diet containing fish meal, we found significant differences in the microbial communities based on both line and diet. This agrees with previous studies where significant differences have been described in the intestinal microbiota of chickens from different lines, including those from faster and slower growing lines [73][74][75]. Differences have also previously been observed in the microbiota when feeding chickens a diet supplemented with fish meal [34,35].…”
Section: Discussionsupporting
confidence: 92%
“…When analysing the abundance of MAGs between birds from different lines, consuming either a vegetable diet or a diet containing fish meal, we found significant differences in the microbial communities based on both line and diet. This agrees with previous studies where significant differences have been described in the intestinal microbiota of chickens from different lines, including those from faster and slower growing lines [73][74][75]. Differences have also previously been observed in the microbiota when feeding chickens a diet supplemented with fish meal [34,35].…”
Section: Discussionsupporting
confidence: 92%
“…2 and 3). Additionally, the age of the animal was the variable that had the highest in uence over the microbiota variation, in agreement with previous studies [48,50]. This is a key evidence suggesting that microbiota approximations done under controlled environments do not differ largely from farming conditions.…”
Section: Discussionsupporting
confidence: 90%
“…This is in agreement with other microbiome studies that observed strong individual variation of microbiome communities in C . elegans (Dirksen et al ., ) and other hosts (Turnbaugh et al ., ; Ainsworth et al ., ; Hernandez‐Agreda et al ., ; Ocejo et al ., ). For instance, a sponge study identified the core microbiome on the operational taxonomic unit level (97% sequence identity) by sampling individuals over 36 months (Bjork et al ., ).…”
Section: Discussionmentioning
confidence: 97%